IMPROVING ESSAY WRITING SKILLS ON ECOLOGICAL THEMES THROUGH A RELIGIOUS QURAN-BASED CRITICAL LITERACY CULTURE - Nurjaman, Muhamad Ichsan; Hamdani, Ripi; Muhamad, Sukardi (Program Studi Pendidikan Bahasa Arab, 2025)
This study aims to improve essay writing skills on ecological themes through the application of a religious Quran-based critical literacy culture. This study uses a quasi-experimental method with a single group pretest-posttest design on third semester students of the Indonesian Language and Literature Education Study Program at Muhammadiyah University Bogor Raya. The results of the study indicate a significant improvement in essay writing skills after the implementation of a critical literacy culture based on the religious values of the Quran. This improvement is demonstrated by higher posttest average scores compared to the pretest, as well as the quality of the students' essays, which reflect more logical arguments, stronger ecological awareness, and the internalization of Islamic values in the structure of the writing